Storage stability of minimally processed pinhão by using edible coatings with antimicrobial characteristics - Moreira, Michele Krüger Vaz; Cantillano, Rufino Fernando Flores; Gandra, Eliezer Avila; Mendonça, Carla Rosane Barboza; Borges, Caroline Dellinghausen (Semina: Ciências Agrárias, 2020)
The pinhão shows high nutritional value; however, its consumption is still low owing to the long cooking time required because it is hard to peel, and it is susceptible to sprouting, larval infestation, and fungal contamination. Thus, this study aimed to evaluate the storage stability of minimally processed pinhão by using edible coatings with antimicrobial characteristics. The pinhões were subjected to minimal processing with the following treatments: Treatment A - control; Treatment B - chitosan; Treatment C - xanthan gum and clove essential oil. After drying, they were packed in polyethylene terephthalate and stored at 4 Â°C for nine days. The pinhões were analyzed for mass loss, total acidity, reducing sugars, vitamin C, color, firmness, respiratory rate, sensory characteristics, and microbial growth. In general, no differences were observed in mass loss, reducing sugars, and oxygen concentrations of the pinhões after any treatment. In addition, we observed a reduction in acidity and carbon dioxide concentrations, maintenance of color parameters, and the absence of growth of thermotolerant coliforms and coagulase-positive Staphylococcus. Although the minimal processing did not increase the respiratory rate of pinhões, it did not stop the process of seed maturation. Of the coatings evaluated, chitosan coating of the pinhões was associated with a higher content of vitamin C as well as a lower number of psychrotrophic microorganisms. The coatings did not influence the taste and aroma of the minimally processed pinhões.